2017
DOI: 10.3389/fimmu.2016.00680
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF and IL-3 Modulate Human Monocyte TNF-α Production and Renewal in In Vitro Models of Trained Immunity

Abstract: GM-CSF and IL-3 are hematopoietic cytokines that also modulate the effector functions of several immune cell subsets. In particular, GM-CSF and IL-3 exert a significant control on monocyte and macrophage effector functions, as assessed in experimental models of inflammatory and autoimmune diseases and also in human studies. Here, we sought to investigate the mechanisms and the extent to which GM-CSF and IL-3 modulate the pro-inflammatory, LPS-mediated, activation of human CD14+ monocytes taking into account th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…Our data seem to target GM-CSF as a pivotal actor of the BG-induced priming of macrophages. Consistently with this hypothesis, GM-CSF-treated macrophages/monocytes exposed to TLR2 or TLR4 ligands were shown to produce significantly more IL-1β, IL-6, and TNFα ( 30 , 40 42 ). Furthermore, GM-CSF was also able to prevent endotoxin tolerance in macrophages by restoring TNFα production on LPS-tolerized human monocytes ( 43 ).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our data seem to target GM-CSF as a pivotal actor of the BG-induced priming of macrophages. Consistently with this hypothesis, GM-CSF-treated macrophages/monocytes exposed to TLR2 or TLR4 ligands were shown to produce significantly more IL-1β, IL-6, and TNFα ( 30 , 40 42 ). Furthermore, GM-CSF was also able to prevent endotoxin tolerance in macrophages by restoring TNFα production on LPS-tolerized human monocytes ( 43 ).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, it was very recently shown that GM-CSF, and IL-3, on its own, was sufficient to train human monocytes in a p38- and SIRT2-dependent manner ( 30 ). In this study, we also observed that GM-CSF pretreatment of mouse macrophages induced a moderate but significant increase of cytokine secretion upon LPS re-stimulation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…T helper (Th) cells, one of subsets of T cells, mediates the production of ILs, which can active immune cells during immune response evidencing by huper-levels of IL-2 activates pro-inflammatory CD4 + T cells (33). IL-3 participates in regulating myeloid cell expansion, autoimmunity and modulate human CD14 + monocyte response in short-term or long-term models of trained immunity (34). IL-6 is a critical factor for maturation, proliferation, differentiation and maintenance of B cells/plasma cells, which seems to enhance the development of pro-inflammatory cell and to inhibit the development T regulatory cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…alveolar macrophages (Rothchild et al, 2017) and facilitating containment of virulent mycobacteria in pulmonary granulomas (Szeliga et al, 2008). Interestingly, GM-CSF along with IL-3 priming of CD14+ human monocytes enhanced TNF production and monocyte renewal (as evaluated by the degree of cell confluency and increased cell number by fluorescence and timelapse microscopy) upon subsequent LPS stimulation, indicating a potential mechanism of trained immunity (Borriello et al, 2016). As detailed in the following sections, trained immunity refers to the ability of innate immune cells to mount an enhanced subsequent response to diverse microbes, a phenomenon whose underlying mechanisms are under intense investigation.…”
Section: Tb-specific Protection Conferred By Bcg Vaccinementioning
confidence: 99%